Changes in the European family (Journal of Parents and Teachers, 2026)
This article provides a summary of the findings of the study seminar on changes in the European family, organised by the Council of Europe in Strasbourg and published in Spain by the Fundación Encuentro. It focuses on changes in family structures and the trends in this regard in various countries. It then analyses in detail the possible causes of these changes and proposes a number of activities to be carried out at the Parents’ School.
Keywords: changes in European families; family structure; young adults; single life